Breaking the Spell: Combating Multidrug Resistant ‘Superbugs’ - Khan, Shahper N.; Khan, Asad U. (Frontiers in Microbiology, 2016)
Multidrug-resistant (MDR) bacteria have become a severe threat to community health. Conventional antibiotics are getting increasingly ineffective as a consequence of resistance, and so it is imperative to realize new antimicrobial strategies. In this review we emphasized the microorganisms primarily reported in the resistance process, the so called ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa, and enterobacteriaceae) accentuating their capacity to “escape” from common antibacterial regimes. The upcoming antimicrobial agents showing great potential and can serve as alternative therapeutic options are discussed. We also provided succinct overview of two evolving technologies; specifically network pharmacology and functional genomics profiling. Furthermore, In vivo imaging techniques can provide novel targets and a real time tool for potential lead molecule assessment. The employment of such approaches at early stages of the drug development enables more informed decisions on candidate drug selection and moreover to maximize or predict efficacy before clinical development.